On Causee in Sason Arabic. (14th June 2022) - Akkuş, Faruk
Abstract: This article aims to understand the syntax of three causative constructions in Sason Arabic. It demonstrates that in geminate causatives and 'give' causatives, the causee is introduced in CauseeP, unlike the embedded agent in 'make' causatives, which embed a thematic VoiceP. Despite differing from Voice 0 $$ {}^0 $$ in several respects, Causee 0 $$ {}^0 $$, like Voice 0 $$ {}^0 $$, exhibits an active–passive‐like alternation, which provides independent evidence for an analysis of the passive that treats it as a subtype of the Voice head. The article further distinguishes between geminates and 'give' causatives on the basis of the (in)compatibility of the causee with an applied argument. In geminates, Causee 0 $$ {}^0 $$ and Appl 0 $$ {}^0 $$ are bundled, and the same argument bears two θ $$ θ $$ ‐roles, whereas in other causative constructions, Causee 0 $$ {}^0 $$ and Appl 0 $$ {}^0 $$ remain separate, with each argument bearing a distinct θ $$ θ $$ ‐role.